The Heme-Oxygenase Family Required for Phytochrome Chromophore Biosynthesis Is Necessary for Proper Photomorphogenesis in Higher Plants - Davis, Seth J. (American Society of Plant Physiologists, 2001)
The committed step in the biosynthesis of the phytochrome chromophore phytochromobilin involves the oxidative cleavage of heme by a heme oxygenase (HO) to form biliverdin IXα. Through positional cloning of the photomorphogenic mutant hy1, the Arabidopsis HO (designated AtHO1) responsible for much of phytochromobilin synthesis recently was identified. Using the AtHO1 sequence, we identified families of HO genes in a number of plants that cluster into two subfamilies (HO1- and HO2-like). The tomato (Lycopersicon esculentum) yg-2 and Nicotiana plumbaginifolia pew1 photomorphogenic mutants are defective in specific HO genes. Phenotypic analysis of a T-DNA insertion mutant of Arabidopsis HO2 revealed that the second HO subfamily also contributes to phytochromobilin synthesis. Homozygous ho2-1 plants show decreased chlorophyll accumulation, reduced growth rate, accelerated flowering time, and reduced de-etiolation. A mixture of apo- and holo-phyA was detected in etiolated ho2-1 seedlings, suggesting that phytochromobilin is limiting in this mutant, even in the presence of functional AtHO1. The patterns of Arabidopsis HO1 and HO2 expression suggest that the products of both genes overlap temporally and spatially. Taken together, the family of HOs is important for phytochrome-mediated development in a number of plants and that each family member may uniquely contribute to the phytochromobilin pool needed to assemble holo-phytochromes.